2016
DOI: 10.1097/jom.0000000000000584
|View full text |Cite
|
Sign up to set email alerts
|

Large Machinery-Related Agricultural Injuries Across a Five-State Region in the Midwest

Abstract: Large machinery-related agricultural injuries can result in significant consequences. Associated increased injury risks require further investigation and targeting of relevant interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Increased risk of machine-related injuries included the following: male gender, increasing age, history of injury, and hours worked. 25 Male individuals, specifically those aged 60 to 89 years, are most likely to die from tractor injuries. 26 Our study demonstrated that those admitted to the ICU were twice as likely to die as those taken to the OR.…”
Section: Discussionmentioning
confidence: 99%
“…Increased risk of machine-related injuries included the following: male gender, increasing age, history of injury, and hours worked. 25 Male individuals, specifically those aged 60 to 89 years, are most likely to die from tractor injuries. 26 Our study demonstrated that those admitted to the ICU were twice as likely to die as those taken to the OR.…”
Section: Discussionmentioning
confidence: 99%
“…In agriculture, long hours and fatigue were thought to be risk factors for injury and illness 37,44,45,47–50,53,56–62 . Sleep disorders 63 and increased work hours, 64,65 were associated with depression.…”
Section: Resultsmentioning
confidence: 99%
“…55 In agriculture, long hours and fatigue were thought to be risk factors for injury and illness. 37,44,45,[47][48][49][50]53,[56][57][58][59][60][61][62] Sleep disorders 63 and increased work hours, 64,65 were associated with depression. A survey of farmers in the United Kingdom found they believed fatigue was the main factor in quad-bike (four-wheeler) loss-of-control incidents, 56 and a survey of farmers in the United States found "hurry, fatigue, and stress" to be the top reasons for a work-related injury.…”
Section: Evidence Of Injury and Illnessmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a bimodal distribution of risk for injuries. Young and inexperienced workers are more prone to injury [1], while older workers are more vulnerable to the impacts of injury from heavy equipment [35] and suffer more extensive and longer disability [36]. Many of the chemical, nuclear and DOE facilities are working with aging workforces partly because of an overall loss of graduate training in these areas.…”
Section: Resultsmentioning
confidence: 99%